Etiological factors of periodontal abscesses: an emerging pathology. A three-case report - Díaz-Caballero, Antonio José; Rivera-Peñates, Diana Marcela; Anaya-Guzmán, Laura Isabel (Universidad y Salud, 2022)
Introduction: Periodontal abscesses are the third most frequent dental emergency (6%-14%). Objective: To describe different etiological factors of periodontal abscesses in three patients. Case description: The first case was a 52-year-old woman who sought treatment due to spontaneous bleeding. During the examination, she revealed bleeding on probing (BP), presence of periodontal pockets (PP), and calculi (C). Scaling and root planning (SRP) was performed as treatment, which was complemented with detoxification with tetracycline and postoperative pharmacological treatment. The second case was a 27-year-old man who came to the clinic due to gum enlargement and showed BP and PP. The lesion was treated and SRP was performed. Finally, the third patient was a 21-year-old male who sought a follow-up consultation. The clinical examination showed the presence of dental calculi and periodontal pockets in teeth 16 and 17. SRP complemented with detoxification with tetracycline and postoperative pharmacology were used as treatments. Conclusion: The etiology of the periodontal abscesses in the first and third cases was based on the lack of depth during root scaling and planning. The cause in the second case was effects of food. Identifying this etiology is useful to achieve proper diagnosis, prognosis and treatment of periodontal abscesses.